1979
DOI: 10.1037/0022-0167.26.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Does the Vocational Exploration and Insight Kit equal the sum of its parts? A comparison study.

Abstract: This study compares the impact of a new vocational intervention, the Vocational Exploration and Insight Kit (VEIK), with the Self-Directed Search (SDS) and the Vocational Card Sort (VCS). Subjects were 103 undergraduate women. Results indicate that the SDS, VCS, and VEIK have small and similar effects on women's vocational behavior. Findings lend support to counselor-free techniques as appropriate and inexpensive methods of career exploration. The use of certain criteria for outcome studies of vocational inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…The self-help interventions were least effective, which may indicate that a counselor needs to be involved in the treatment. Although Graff, Danish, and Austin (1972), Krivatsy and Magoon (1976), and Talbot and Birk (1979) encouraged the use of counselor-free interventions (i.e., selfhelp), the results of the present analyses do not support the universal application of those practices. The suggestions by Bodden and James (1976), Stripling (1976, 1977), and Sampson and Stripling (1979) that self-help treatment should be used only to augment the services of the counselor would be more appropriate.…”
Section: Classification According To Length Of Treatmentcontrasting
confidence: 85%
“…The self-help interventions were least effective, which may indicate that a counselor needs to be involved in the treatment. Although Graff, Danish, and Austin (1972), Krivatsy and Magoon (1976), and Talbot and Birk (1979) encouraged the use of counselor-free interventions (i.e., selfhelp), the results of the present analyses do not support the universal application of those practices. The suggestions by Bodden and James (1976), Stripling (1976, 1977), and Sampson and Stripling (1979) that self-help treatment should be used only to augment the services of the counselor would be more appropriate.…”
Section: Classification According To Length Of Treatmentcontrasting
confidence: 85%
“…Previous research has consistently indicated that VCS (e.g., Cooper, 1976;Slaney & Dickson, 1985) and SDS (Krivatsy & Magoon, 1976;Takai & Holland, 1979;Talbot & Birk, 1979) are effective in stimulating a greater number of vocational options. SIGI + also significantly increased oc;-cupational options for students compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Five of six investigations (Cooper 1976, Slaney 1978, Lawler 1979, Talbot & Birk 1979, Atanasoff & Slaney 1980), using high school or college samples, indicate that use of a vocational card sort in which there is no keying or structure does not yield more options than a structured interest inventory. Both produce more options, but card sorts lack any quality control; any option stimulated by the use of a vocational card sort is counted as a valid option ---o ccupational alternatives that are consistent or inconsistent with a per son's measured interests.…”
Section: Inventory Effects and Controversymentioning
confidence: 99%
“…Another provocative fi nding-the failure to produce larger effects by piling similar or diverse treatments together (Miller & Cochran 1979, Talbot & Birk 1979)-also implies the need to develop integrated treatment chains that are more beneficial than the individual links. In addition, we need some explanation of why many brief treatments appear to be as effective as long-term treatments (cf course outcomes with counselors).…”
Section: Some Interpretationsmentioning
confidence: 99%